2019
DOI: 10.1016/j.colsurfb.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

On the rheology of pulmonary surfactant: Effects of concentration and consequences for the surfactant replacement therapy

Abstract: The role of pulmonary surfactant is to reduce the surface tension in the lungs and to facilitate breathing. Surfactant replacement therapy (SRT) aims at bringing a substitute by instillation into the airways, a technique that has proven to be efficient and lifesaving for preterm infants. Adapting this therapy to adults requires to scale the administered dose to the patient body weight and to increase the lipid concentration, whilst maintaining its surface and flow properties similar. Here, we exploit a magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(59 citation statements)
references
References 52 publications
8
51
0
Order By: Relevance
“…It is interesting to point out that the surface shear rheology of spread PS films showed a frequency dependency similar to that of the surface dilational rheology determined here. It was found that both the shear elastic and viscous moduli of DPPC-containing monolayers (46) and natural PS preparations (47,48) (including Infasurf and Curosurf) increase with frequency in the same frequency range as studied here. Dilational rheology and shear rheology represent different rheological properties of thin films (49).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is interesting to point out that the surface shear rheology of spread PS films showed a frequency dependency similar to that of the surface dilational rheology determined here. It was found that both the shear elastic and viscous moduli of DPPC-containing monolayers (46) and natural PS preparations (47,48) (including Infasurf and Curosurf) increase with frequency in the same frequency range as studied here. Dilational rheology and shear rheology represent different rheological properties of thin films (49).…”
Section: Discussionsupporting
confidence: 66%
“…In terms of PS film, the surface dilational rheology provides information on the composition of the PS film, which is important for understanding phase transitions and film collapse during normal tidal breathing. Surface shear rheology provides information on the stability of PS films, which is crucial to better understand the spreading and Marangoni flow of PS films (46)(47)(48)50). The finding that both dilational moduli and shear moduli of PS films increase with frequency may have implications in better understanding the biophysical stability of the PS films, thus contributing to the design of novel, to our knowledge, surfactant preparations for pulmonary drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Below 10 -3 g L -1 , the viscosity remains at the level of the pristine fluid around = 9.0 ± 2.0 mPa s. This value agrees well with the recent measurements obtained on Curosurf® as a function of the lipid content. 36 With increasing 31 , a similar behavior is observed with the two particles studied. The static viscosity decreases down to 5 ± 1 mPa s and for silica the tendency persists towards the highest concentrations.…”
Section: Ii3 -Alumina Loaded Surfactant Showing a Soft Solid Behaviorsupporting
confidence: 73%
“…For calibration, MRS was performed on a series of water-glycerol mixtures of increasing viscosities, 4.95, 34.9, 48.9 and 80.0 mPa s, corresponding to glycerol concentrations of 49.8%, 81.0%, 84.5% and 89% (T = 25 °C), leading to a susceptibility anisotropy coefficient Δ = 0.054 ± 0.006 (Supplementary Information S13). 36 deaux 1) for the synthesis of the aminated silica nanoparticles. ANR (Agence Nationale de la Recherche) and CGI (Commissariat à l'Investissement d'Avenir) are gratefully acknowledged for their financial support of this work through Labex SEAM (Science and Engineering for Advanced Materials and devices) ANR 11 LABX 086, ANR 11 IDEX 05 02.…”
Section: Active Microrheology (Including Sample Preparation)mentioning
confidence: 99%
“…This stands in contradistinction to non-living matter, where this intermittent behavior is not observed. 38,40,42,57 In the steady rotation phases, the analysis of the wire motion leads to the conclusion that the cytoplasm of murine NIH/3T3 fibroblasts is similar to a viscoelastic liquid and equivalent to a Generalized Maxwell fluid model. The shear viscosity 𝜂 and elastic modulus 𝐺are retrieved from these measurements and are in agreement with earlier reports.…”
Section: Discussionmentioning
confidence: 99%